Effect of Nano-hydroxyapatite Toothpaste on Microhardness of Primary Teeth Enamel in Comparison with Two other Toothpastes "An in Vitro Study" - Marwa Mohamed; Reham Elghazawy; Amr Abd El-Aziz (Ain Shams University, Faculty of Dentistry, 2024)
Aim: The purpose of the current study was to investigate a nano-hydroxyapatite toothpaste in primary teeth in comparison with two other kinds of toothpaste (fluoride and miswak) regarding their effect on the microhardness of enamel by the Vickers hardness test and surface topography using scanning electron microscopy (SEM). Materials and methods: First, forty extracted primary molars were obtained from the outpatient clinic of the Pediatric Dentistry Department, Faculty of Dentistry, Ain Shams University. Second, samples were grouped into four main groups according to the type of toothpaste used. Group 1: n = 10 specimens were brushed with nanohydroxyapatite toothpaste. Group 2: n=10 specimens were brushed with fluoride toothpaste. Group 3: n=10 specimens were brushed with Miswak toothpaste. Group 4: n=10 specimens were immersed in distilled water. Third, specimens were subjected to a microhardness test (the Vicker test) before and after the remineralization stage. Representative specimens from the Nano-HA groups, the positive control group, and the negative control group were selected at random for SEM sample preparation. These were analyzed using a scanning electron microscope. Results: The most significant finding was achieved in NHAP, followed by fluoride and then miswak, whereas the value was found to be at its lowest in distilled water.Conclusion: NHA toothpaste exerted remineralizing effects on the artificial carious lesion.